Development of Interactive Flash Card Media in Cultural Diversity Learning - Muhammad Sofirin; Rahim, Abdul; Najib, Khotim Hanifudin (International Journal of Education Research and Development, 2025)
This study aims to: 1) Develop interactive learning media in the form of flash cards on the subject of cultural diversity for fourth grade elementary school students; 2) Describe the feasibility of interactive flash card learning media based on validation by material experts and media experts; and 3) Determine students' responses to interactive flash card learning media in cultural diversity learning. This study is a type of research and development (Research and Development) that uses the ADDIE model, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects in this study were fourth grade students of SD Negeri 1 Trirenggo Bantul, while the object of the study was interactive flash card learning media on cultural diversity material. The feasibility assessment was carried out by material experts and media experts, while data was collected through observation, interviews, validation questionnaires, and student response questionnaires. The data analysis technique used a quantitative and qualitative descriptive approach. The results of the study showed that: 1) This interactive flash card learning media consists of three main parts, namely the beginning, the core, and the end. The beginning contains the cover display, the purpose of media development, and instructions for use. The core section displays the main content in the form of interactive pictures of traditional houses, traditional clothing, and regional musical instruments, equipped with explanatory video links in the underlined text.